The doctor to the dead : grotesque legends and folk tales of old Charleston - Bennett, John, 1865-1956 (University of South Carolina Press, 2020)
"You ask for a story. I will tell you one, fact for fact and true for true ..." So begins "Crook-Neck Dick," one of twenty-three stories in this beguiling collection of Charleston lore. Derived from African-American legends, these fables have entertained generations of Charlestonians with sheer storytelling magic. To the delight of folklorists, students of Charleston history, and all those who love a good ghost story, this treasury returns to print in a new edition featuring previously unpublished photos of the storytellers who shared these remarkable stories with John Bennett"--